Systematic and Statistical Analysis of Public Knowledge of Marijuana Addiction and Psychosis Mental Health Outcome Youths in Calabar - Dorn Cklaimz Enamhe; E. E. Tangban; Mary U. Ojong-Ejoh; Beauty U. Kenneth; Rose U. Agba; Ojong Tabe Ejoh (PT Mattawang Mediatama Solution, 2022)
Nigeria ranks among the highest consumers of marijuana global and the youths are among the highest demographic of consumers. But there is dearth of evidence that people know about the dangers inherent in being addicted to marijuana. This study examined public knowledge of marijuana addiction and risk of psychosis mental health outcome among youths in Calabar. The survey method through the distribution of self-administered semi structured was used to elicit data from a sample of 384, selected from Calabar, Cross River State, Nigeria using the stratified, purposive and random sampling technique. Data collected was analyzed using descriptive statistics using such as frequency distribution, percentages, figures and inferential statistics in the form of independent T-test. Results revealed that there is public knowledge of the marijuana addiction and psychotic. there is need for the government and its Drug enforcement agency to formulate drastic laws and put in place punitive measures that will curb the distribution, sale and consumption of marijuana